Ecophysiological screening of tree species for biomass production: trade‐off between production and water use. Issue 11 (20th November 2013) - Wang, Dan; LeBauer, David; Kling, Gary; Voigt, Thomas; Dietze, Michael C.
Abstract : Trees are an important biomass source for cellulosic ethanol production. The ability to identify tree species that are efficient in balancing water loss and carbon uptake based on physiological traits associated with growth and water use is useful for screening candidate species and genotypes. We used a common‐garden approach to evaluate the relationships between traits, productivity, and WUE among 21 tree species across two growing seasons. Species differed significantly in leaf‐level gas exchange, Δ 13 C, phenology and growth. Robinia pseudoacacia, Populus deltoides, Catalpa speciosa, Rhus copallinum, and Acer saccharinum had higher total height (Ht) and basal diameter (DB) growth than the other species. Δ 13 C scaled positively with growth rate and negatively with intrinsic WUE, suggesting that Δ 13 C could be an effective proxy for productivity and WUE for the species evaluated. Principle component analysis indicated that among the faster‐growing species (high Ht and Anet ), Robinia pseudoacacia distinguished itself by a higher Δ 13 C and lower PNUE, while Populus deltoides, Rhus copallinum, Catalpa speciosa and Platanus occidentalis had a higher PNUE and lower Δ 13 C, making it possible to select trees that could optimize the trade‐off between carbon gain and water use and provide guidelines for policy making. Systematic measurements of gas exchange across the growing season are essential for validation of growth models and to elucidate the physiological basis for observed differences in productivity and WUE. Parameters such as Anet, SLA, Nmass, and Δ 13 C give very useful information for future breeding programs having goals of improving woody species productivity and WUE.